Arcada coronária --- uma anomalia rara da circulação coronária - Abreu, G (2014)
Intercoronary communication or 'coronary arcade' is a rare congenital coronary anomaly. We present the case of a 65-year-old man with atypical chest pain for four months. The 12-lead ECG and echocardiogram were normal. Treadmill exercise testing was interrupted at peak exercise due to consecutive salvos of ventricular premature beats, without significant ST-T changes. Coronary angiography showed no significant coronary stenosis, but a connection between the right coronary and circumflex arteries was observed, consistent with coronary arcade. The functional importance of this variant is not clear, but it may cause myocardial ischemia by coronary steal or function as a natural bypass, in which case it may play a protective role in the myocardium if significant atherosclerosis develops.